Determinants of Sharia Banking Market Share in Indonesia - Syarvina, Wahyu; Sugianto, Sugianto (UNISSULA, 2023)
Market Share Ratio can be used to measure the performance of Islamic Banks which are relatively new in Indonesia. The greater the market share of Islamic banks in Indonesia, the greater their role and function for the national economy. Market share is often used as an indicator by companies to see the existence of strength in the market and how important the company is. This research method uses a quantitative approach with an associative method with a population in the form of data on Financial Statements of Islamic Banking in Indonesia during the period 2018 to 2022. The sampling technique was carried out using purposive sampling. The results showed that by using a significance level of 5 percent, the significance value was < 0.05 (0.000 < 0.05), the CAR, ROA, FDR and NPF variables simultaneously (together) had an effect on the market share of Islamic banks in Indonesia. And each variable Capital Adequacy Ratio (CAR), Variable Return On Assets (ROA), Financing to Deposit Ratio (FDR), Non Performing Financing (NPF) partially has a significant positive effect on the Market Share of Islamic Banks in Indonesia.